(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the Coordination between the Ombudsman and Law Enforcement Parties in Handling Maladministration Complaints in Makassar City. The method used in this research is descriptive qualitative with 9 informants. This research information was collected through observation, interviews, and documentation. The results of this study indicate that, not all reports/complaints processed by the Ombudsman must meet the formal and material requirements and some reports are outside the scope of the Ombudsman. Meetings/meetings are often held by the Ombudsman with law enforcement officials, but in the regulatory aspect there is no synergy so that it hampers the resolution of cases. Communications carried out by the Ombudsman with law enforcement authorities and the reported superiors so far have only been limited to resolving cases, so the communication is somewhat less intense. Furthermore, the division of work of the Makassar City Ombudsman seen from the main tasks and functions is in accordance with their respective abilities and expertise, but due to limited human resources, the division of labor is still uneven.